Multi-faceted role of melatonin in neuroprotection and amelioration of tau aggregates in alzheimer's disease - Balmik, Abhishek Ankur; Chinnathambi, Subashchandrabose (Journal of Alzheimers Disease, 2018)
Alzheimer's disease (AD) is one of the major age related neurodegenerative diseases whose pathology arises due to the presence of two distinct protein aggregates, viz., amyloid-beta plaques in extracellular matrix and tau neurofibrillary tangles in neurons. Multiple factors play a role in AD pathology, which includes familial mutations, oxidative stress, and post-translational modifications. Melatonin is an endocrine hormone, secreted during darkness, derived from tryptophan, and produced mainly by the pineal gland. It is an amphipathic molecule, which makes it suitable to cross not only blood-brain barrier, but also to enter several other subcellular compartments like mitochondria and endoplasmic reticulum. In this context, the neuroprotective effect of melatonin may be attributed to its role as an antioxidant. Melatonin's pleiotropic function as an antioxidant and neuroprotective agent has been widely studied. However, its direct effect on the aggregation of tau and amyloid-beta needs to be explored. Furthermore, an important aspect of its function is its ability to regulate the process of phosphorylation of tau by affecting the function of kinases and phosphatases. In this review, we are focusing on the pleiotropic function of melatonin on the aspect of its neuroprotective function in tau pathology, which includes antioxidant function, regulation of enzymes, including kinases and enzymes involved in free radical scavenging and mitochondrial protection.
Keywords: Alzheimer's disease; hyperphosphorylation; melatonin; mitochondria; Protein aggregation; tau protein

Microglial priming of antigen presentation and adaptive stimulation in Alzheimer's disease - Das, Rashmi; Chinnathambi, Subashchandrabose (Cellular and Molecular Life Sciences, 2019)
The prominent pathological consequences of Alzheimer's disease (AD) are the misfolding and mis-sorting of two cellular proteins, amyloid-beta and microtubule-associated protein Tau. The accumulation of toxic phosphorylated Tau inside the neurons induces the increased processing of amyloid-beta-associated signaling cascade and vice versa. Neuroinflammation-driven synaptic depletion and cognitive decline are substantiated by the cross talk of activated microglia and astroglia, leading to neuron degeneration. Microglia are the brain-resident immune effectors that prove their diverse functions in maintaining CNS homeostasis via collaboration with astrocytes and T lymphocytes. Age-related senescence and chronic inflammation activate microglia with increased pro-inflammatory markers, oxidative damage and phagocytosis. But the improper processing of misfolded protein via lysosomal pathway destines the spreading of 'seed' constituents to the nearby healthy neurons. Primed microglia process and present self-antigen such as amyloid-beta and modified Tau to the infiltrated T lymphocytes through MHC I/II molecules. After an effective conversation with CD4(+) T cells, microglial phenotype can be altered from pro-active M1 to neuro-protective M2 type, which corresponds to the tissue remodeling and homeostasis. In this review, we are focusing on the change in functionality of microglia from innate to adaptive immune response in the context of neuroprotection, which may help in the search of novel immune therapy in AD.

Molecular cobalt(II) complexes for tau polymerization in Alzheimer's disease - Gorantla, Nalini Vijay; Landge, Vinod G.; Nagaraju, Pramod Gudigenahally; Priyadarshini, Poornima C. G.; Balaraman, Ekambaram; Chinnathambi, Subashchandrabose (ACS Omega, 2019)
Tau is an axonal protein known to form abnormal aggregates and is the biomarker of Alzheimer's disease. Metal-based therapeutics for inhibition of Tau aggregation is limited and rarely reported in contemporary science. Here, we report the first example of rationally designed molecular cobalt(II)-complexes for effective inhibition of Tau and disaggregation of preformed Tau fibrils. The mechanistic studies reveal that prevention of Tau aggregation by cobalt-based metal complexes (CBMCs) is concentration-dependent and Tau seldom exhibits conformational changes. Interestingly, CBMCs play dual role in causing disassembly of preformed aggregates as well as inhibition of complete Tau aggregation. Furthermore, CBMCs were nontoxic and maintained the tubulin network intact. CBMCs also prevented okadaic acid-induced toxicity in SH-SY5Y cells thus, preventing hyperphosphorylation of Tau. We believe that this unprecedented finding by the newly developed molecular complexes has a potential toward metal-based therapeutics for Alzheimer's disease.

Melatonin interacts with repeat domain of Tau to mediate disaggregation of paired helical filaments - Balmik, Abhishek Ankur; Das, Rashmi; Dangi, Abha; Gorantla, Nalini Vijay; Marelli, Udaya Kiran; Chinnathambi, Subashchandrabose (Biochimica Et Biophysica Acta-General Subjects, 2020)
Tau is the major neuronal protein involved in the stabilization of microtubule assembly. In Alzheimer's disease, Tau self-assembles to form intracellular protein aggregates which are toxic to cells. Various methods have been tried and tested to restrain the aggregation of Tau. Most of the agents tested for this purpose have limitations in their effectiveness and availability to neuronal cells. We have tested melatonin, a neurohormone secreted by pineal gland and a well-known anti-oxidant, for its ability to interact with the repeat domain of Tau using ITC and NMR. In aggregation inhibition and disaggregation studies of repeat Tau, melatonin was found to modulate the aggregation propensity of repeat Tau at a concentration of 5000 mu M and was more effective in dissolving preformed aggregates rather than acting as an aggregation inhibitor. However, there were no major conformational changes in Tau in presence of melatonin as observed by CD spectroscopy. On the basis of our findings, we are proposing a mechanism by which melatonin can interact with the repeat domain of Tau and exhibit its disaggregation effect.
Keywords: Alzheimer's disease; Disaggregation; melatonin; Paired helical filaments; tau protein; Tauopathies

Melatonin reduces GSK3 beta-mediated tau phosphorylation, enhances Nrf2 nuclear translocation and anti-inflammation - Das, Rashmi; Balmik, Abhishek Ankur; Chinnathambi, Subashchandrabose (ASN Neuro, 2020)
Alzheimer's disease is a neuropathological condition with abnormal accumulation of extracellular Amyloid-beta plaques and intracellular neurofibrillary tangles of Microtubule-associated protein Tau (Tau) in the brain. In pathological conditions, Tau undergoes post-translational modifications such as hyperphosphorylation by the activity of cellular kinases, which eventually leads to protein aggregation in neurons. Melatonin is a neuro-hormone that is mainly secreted from the pineal gland and functions to modulate the cellular kinases. In our study, we have checked the neuroprotective function of Melatonin by MTT and LDH assay, where Melatonin inhibited the Tau aggregates-mediated cytotoxicity and membrane leakage in Neuro2A cells. The potency of Melatonin has also been studied for the quenching of intracellular reactive oxygen species level by DCFDA assay and caspase 3 activity. Melatonin was shown to reduce the GSK3 beta mRNA and subsequent protein level as well as the phospho-Tau level (pThr181 and pThr212-pSer214) in okadaic acid-induced Neuro2A cells, as observed by western blot and immunofluorescence assay. Further, Melatonin has increased the cellular Nrf2 level and its nuclear translocation as an oxidative stress response in Tauopathy. The Melatonin was found to induce pro- and anti-inflammatory cytokines levels in N9 microglia. The mRNA level of cellular kinases such as as-GSK3 beta, MAPK were also studied by qRT-PCR assay in Tau-exposed N9 and Neuro2A cells. The immunomodulatory effect of Melatonin was evident as it induced IL-10 and TGF-beta cytokine levels and activated MAP3K level in Tau-exposed microglia and neurons, respectively. Melatonin also downregulated the mRNA level of pro-inflammatory markers, IL-1 beta and Cyclooxygenase-2 in N9 microglia. Together, these findings suggest that Melatonin remediated the cytokine profile of Tau-exposed microglia, reduced Tau hyperphosphorylation by downregulating GSK3 beta level, and alleviated oxidative stress via Nrf2 nuclear translocation.
Keywords: Alzheimer’ Anti-inflammatory; GSK3β melatonin; microglia; neurodegeneration; Nrf2; s disease; Tau hyperphosphorylation

Methylation as a key regulator of Tau aggregation and neuronal health in Alzheimer's disease - Balmik, Abhishek Ankur; Chinnathambi, Subashchandrabose (Cell Communication and Signaling, 2021)
Neurodegenerative diseases like Alzheimer's, Parkinson's and Huntington's disease involves abnormal aggregation and accumulation of toxic proteins aggregates. Post-translational modifications (PTMs) of the causative proteins play an important role in the etiology of disease as they could either slow down or accelerate the disease progression. Alzheimer disease is associated with the aggregation and accumulation of two major protein aggregates-intracellular neurofibrillary tangles made up of microtubule-associated protein Tau and extracellular Amyloid-beta plaques. Post-translational modifications are important for the regulation of Tau`s function but an imbalance in PTMs may lead to abnormal Tau function and aggregation. Tau methylation is one of the important PTM of Tau in its physiological state. However, the methylation signature on Tau lysine changes once it acquires pathological aggregated form. Tau methylation can compete with other PTMs such as acetylation and ubiquitination. The state of PTM at these sites determines the fate of Tau protein in terms of its function and stability. The global methylation in neurons, microglia and astrocytes are involved in multiple cellular functions involving their role in epigenetic regulation of gene expression via DNA methylation. Here, we have discussed the effect of methylation on Tau function in a site-specific manner and their cross-talk with other lysine modifications. We have also elaborated the role of methylation in epigenetic aspects and neurodegenerative conditions associated with the imbalance in methylation metabolism affecting global methylation state of cells.
Keywords: Aggregation; Epigenetics; methylation; Methyltransferases; post-translational modifications; Tau

Microglial remodeling of actin network by Tau oligomers, via G protein-coupled purinergic receptor, P2Y12R-driven chemotaxis - Das, Rashmi; Chinnathambi, Subashchandrabose (Traffic, 2021)
Alzheimer's disease (AD) is associated with age-related neurodegeneration, synaptic deformation and chronic inflammation mediated by microglia and infiltrated macrophages in the brain. Tau oligomers can be released from damaged neurons via various mechanisms such as exosomes, neurotransmitter, membrane leakage etc. Microglia sense the extracellular Tau through several cell-surface receptors and mediate chemotaxis and phagocytosis. The purinergic receptor P2Y12R recently gained interest in neurodegeneration for neuro-glial communication and microglial chemotaxis towards the site of plaque deposition. To understand the effect of extracellular Tau oligomers in microglial migration, the P2Y12R-mediated actin remodeling, reorientation of tubulin network and rate of migration were studied in the presence of ATP. The extracellular Tau species directly interacted with P2Y12R and also induced this purinoceptor expression in microglia. Microglial P2Y12R colocalized with remodeled membrane-associated actin network as a component of migration in response to Tau oligomers. As an inducer of P2Y12R, ATP facilitated the localization of P2Y12R in lamellipodia and filopodia during accelerated microglial migration. The direct interaction of extracellular Tau oligomers with microglial P2Y12R would facilitate the signal transduction in both way, directional chemotaxis and receptor-mediated phagocytosis. These unprecedented findings emphasize that microglia can modulate the membrane-associated actin structure and incorporate P2Y12R to perceive the axis and rate of chemotaxis in Tauopathy.
Keywords: actin remodeling; Alzheimer' chemotaxis; microglia; migration; s disease; Tau Oligomers

Microglia degrade Tau oligomers deposit via purinergic P2Y12-associated podosome and filopodia formation and induce chemotaxis - Chinnathambi, Subashchandrabose; Das, Rashmi (Cell and Bioscience, 2023)
BackgroundTau protein forms neurofibrillary tangles and becomes deposited in the brain during Alzheimer's disease (AD). Tau oligomers are the most reactive species, mediating neurotoxic and inflammatory activity. Microglia are the immune cells in the central nervous system, sense the extracellular Tau via various cell surface receptors. Purinergic P2Y12 receptor can directly interact with Tau oligomers and mediates microglial chemotaxis via actin remodeling. The disease-associated microglia are associated with impaired migration and express a reduced level of P2Y12, but elevate the level of reactive oxygen species and pro-inflammatory cytokines.ResultsHere, we studied the formation and organization of various actin microstructures such as-podosome, filopodia and uropod in colocalization with actin nucleator protein Arp2 and scaffold protein TKS5 in Tau-induced microglia by fluorescence microscopy. Further, the relevance of P2Y12 signaling either by activation or blockage was studied in terms of actin structure formations and Tau deposits degradation by N9 microglia. Extracellular Tau oligomers facilitate the microglial migration via Arp2-associated podosome and filopodia formation through the involvement of P2Y12 signaling. Similarly, Tau oligomers induce the TKS5-associated podosome clustering in microglial lamella in a time-dependent manner. Moreover, the P2Y12 was evidenced to localize with F-actin-rich podosome and filopodia during Tau-deposit degradation. The blockage of P2Y12 signaling resulted in decreased microglial migration and Tau-deposit degradation.ConclusionsThe P2Y12 signaling mediate the formation of migratory actin structures like- podosome and filopodia to exhibit chemotaxis and degrade Tau deposit. These beneficial roles of P2Y12 in microglial chemotaxis, actin network remodeling and Tau clearance can be intervened as a therapeutic target in AD.
Keywords: Filopodia; microglia; migration; Podosome; Tau Oligomers

Macrocyclic peptides derived from AcPHF6*and AcPHF6 to selectively modulate the Tau aggregation - Dangi, Abha; Qureshi, Tazeen; Chinnathambi, Subashchandrabose; Marelli, Udaya Kiran (Bioorganic Chemistry, 2024)
Ten macrocyclic peptides, each comprising 14 amino acids, were designed and synthesized based on the Tau aggregation model hexapeptides AcPHF6* and AcPHF6. The design took into account the aggregation tendencies of each residue in AcPHF6* and AcPHF6, their aggregation models, while employing peptide-based structural design principles including N-methylation to promote turns and to block hydrogen bond propagation and elongation of the aggregation chain. NMR analysis supported that all these peptides adopted an antiparallel beta-sheet conformation. Self-aggregation studies characterized the aggregation properties of these peptides, identifying two peptides with the highest (P3) and lowest (P8) aggregation tendencies. In cross-aggregation studies with the parent peptides AcPHF6* and AcPHF6, P3 and P8 were found to promote and reduce aggregation, respectively. Furthermore, P3 and P8 demonstrated an enhancement and diminution effect on the aggregation of K18wt, indicating their capacity to modulate aggregation even at the macromolecular level. Thus, the two simple peptides, P3 and P8 selectively exhibit pro- or anti-aggregation effects on PHF peptides and Tau. This study, has thus developed structurally well-defined non-complex peptides, derived from AcPHF6* and AcPHF6, to modulate Tau aggregation as desired, offering applications in Tau model studies and the development of Tau aggregation inhibitors or promoters.
Keywords: Cyclic peptides; Peptide -based drug design (PBDD); Peptide conformation; PHF peptides; Tau Aggregation